Environmental-friendly Eco-labeling Matters: Evidences From an ERPs Study - Jin, Jia; Dou, Xiaodong; Meng, Liang; Yu, Haihong (Frontiers in Human Neuroscience, 2018)
The sustainable development of resources is currently considered an important topic. In order to protect the environment and reward sustainable practices, eco-labeling is already widely promoted in many regions around the world, signifying the environmental friendliness of the labeled food. It is of great importance to study consumers’ attitudes toward eco-labeled food since food is produced to satisfy consumers’ needs. The present study employed event-related potentials to investigate consumers’ attitudes toward eco-labeled food by comparing their neural processing of visual stimuli showing eco-labeled and non-labeled food. Our results showed that behaviorally, participants preferred to buy eco-labeled food rather than non-labeled food. At the brain level, we observed markedly smaller P2 and N2 amplitudes when pictures of eco-labeled food were presented. Furthermore, we also found that the amplitude of P2 was negatively correlated with participants’ purchase intention. Therefore, our current findings may support the notion that although the environmental friendliness eco-label was not benefit for participants’ own interest, it would also induce consumers’ positive emotion and less cognitive conflict to the product and then result in a greater purchasing intention. This may be affected by the delivered values of social desirability.